Polycarbonate : antimicrobial polymer delivery, monomer synthesis, rapid polymerization and functionalization - Tan, Eddy Wei Ping (Nanyang Technological University, 2021)
Ring-opening polymerization of cyclic carbonate monomers is the most common method used to synthesize a range of polycarbonates with unique properties for various applications. This thesis will explore three different areas related to the field of polycarbonates. The first chapter will examine the therapeutic potential of coacervates formed through the complexation of positively charged guanidinium-functionalized antimicrobial polycarbonate with diblock copolymers composed of methoxy poly(ethylene glycol) and negatively charged polycarbonate. The second chapter presents two novel and simple synthetic routes to access cyclic carbonate monomers in bulk while avoiding the use of highly toxic phosgene or chloroformate reagents and tedious protection-deprotection protocols. In the final chapter, the post-polymerization routes for polycarbonate platform were expanded through the development of two new functionalization routes using para-fluoro-thiol SNAr substitution reaction.